PROFESSIONAL BURNOUT IN SPEECH AND LANGUAGE THERAPY PRACTICE - Samra Jusufbašić; Leila Begić; Amela Abidović- Mačković (Research in Education and Rehabilitation, 2025)
The “burnout” syndrome is a state of emotional, physical, and mental exhaustion caused by excessive and prolonged stress. It is also referred to as a disease of the modern age. It most commonly occurs after an individual experiences emotional exhaustion and an inability to meet constant demands, leading to a loss of interest and motivation in their work. The profession of a speech and language therapist is considered a helping profession that can lead to burnout syndrome. The main aim of this research was to examine the level of professional burnout in speech and language therapy practice. The sample consisted of 69 speech and language therapists of both genders, employed in various institutions. The results showed that 31 therapists (44.8%) exhibited varying degrees of professional burnout, ranging from mild burnout to burnout requiring professional assistance, while 38 therapists (55.1%) showed no signs of professional burnout. No statistically significant difference in the level of professional burnout was found in relation to the gender of the therapists, but a statistically significant difference was found in relation to the age of the therapists. The results indicated that there is no difference in the level of professional burnout in relation to years of service, nor a statistically significant correlation between the level of professional burnout and the type of institution where the therapists are employed, working hours during the week, or the number of treatments conducted during the working day. Taking care of the mental health of speech and language therapists is a very important factor that contributes to the quality and efficiency of conducting speech and language prevention, assessment, diagnostics, and treatment.